POPULARIZING EPIC NARRATIVE IN GEORGE R.R. MARTIN'S A GAME OF THRONES - Ida Rochani Adi (Humaniora, 2012)
This research is intended to show the sustainability of epic in latest years of human history through the most phenomenal fantasy in American literature, A Game of Thrones. Along with the capability of human beings in thinking dearly and sensibly, it is commonsensical that people tend to free themselves from irrationality. The reality shows, however, that the existence of epic fantasy still has power in appealing audiences or readers. This is the case with A Game of Thrones written by George RR Martin who was given the award of One of The Most Influential People in 2011 by Time magazine. This qualitative march, using genre approach, finds out that in order to be compatible with today's society, an epic seen in A Game of Thrones, which is commonly known as a story centering on the legendary hero and his heroic deed in oral folk tradition, keeps its power as an epic fantasy narrative through certain archetypes and formulas. Through genre analysis using semiotic approach, the research brings about conclusions that the elements of high fantasy, elements built through rational representation, and a smart combination of convention and invention brings about its popularity. It is also concluded that there is a close relationship between the myth and the mode of people living even in the most modern context.